(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article discusses the speciﬁ c of social myths, peculiarities of functioning of myths in modern world. Modern myths and their content and form are quite different from the ancient myths. But as the ancient myths, they acquire the consciousness of the masses and move their activity to the appropriate channel. Especially a lot of faith in these myths appear in crisis times for the society (war, strife, revolution, destruction), when the old values rapidly were destroyed and new ones are just beginning to emerge. With regard to modern myths we can talk about the latent and active phases of their operation. Myth becomes the dominant of society during its active phase, expanding its inﬂ uence to the size of the whole community or a large part of it. When social expectations are changing, the myth is losing its former «glory», giving place to the other ideological model and drastically reducing the number of its adherents. However, when typologically similar historical conditions (based on the next turn of expectations of society) appear, the old myth may be required by society and once again become the dominant ideology. You must also remember that the mythological thinking in the modern world has been transformed form, in particular, the degree of development of human consciousness as a result of social evolution.